Regulatory and Accountability Pressures in CSR and ESG Reporting: A Review of The Transition From Voluntary to Mandated Disclosure - Cheryl Gem D. Abraham; Anik Yuesti; Joel Arante Alve (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
The global landscape of corporate social responsibility (CSR) and environmental, social, and governance (ESG) reporting has undergone a significant transformation, shifting from predominantly voluntary disclosures toward increasingly mandatory regulatory regimes. This literature review examines the regulatory and accountability pressures driving this transition and analyzes their implications for corporate transparency, disclosure quality, and stakeholder trust. Drawing on prior empirical and conceptual studies, the review synthesizes evidence on how mandatory reporting frameworks influence firm behavior, reporting comparability, and accountability mechanisms. A firm level practice illustration is included to contextualize how organizations respond to evolving regulatory expectations. The review finds that while mandatory ESG reporting enhances transparency and comparability, challenges persist regarding enforcement consistency, reporting burdens, and potential unintended market reactions. The study contributes to the literature by integrating regulatory, accountability, and firm-level perspectives, offering insights for policymakers, researchers, and practitioners navigating the evolving ESG reporting environment.